TDP-43 in ALS: Stay on target… Almost there - Jovičić, Ana (2014)
ALS is associated with RNA processing impairments involving the RNA-binding protein TDP-43. Pioneering a novel RNA beacon to illuminate RNA trafficking in neurons, Alami et al. discover a novel cytoplasmic function for TDP-43, suggesting a new disease mechanism.